Pulse current enhanced MOF-based catalyst as well as preparation method and application thereof
The MOF-based catalyst of Cu nanoparticles is solved by processing pulsed current, and the problems of poor product selectivity and low activity of Cu-based catalysts in CO2 electroreduction are achieved, efficient multi-carbon product catalysis is achieved, and the utilization value of CO2 resources is enhanced.
Patent Information
- Application Number
- CN202411374770.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-29
AI Technical Summary
During the electroreduction of CO2, Cu-based catalysts have poor product selectivity and low activity, making it difficult to efficiently synthesize polycarbon products, which limits the high-value utilization of CO2 resources.
Using the preparation method of pulse current-enhanced MOF-based catalyst, an active center is generated in situ in the two-dimensional MOF-based material Cu-TCPP, and the Cu nanoparticles are treated with pulse current to change their surface state, and catalytic activity and selectivity are enhanced.
The reaction selectivity and efficiency of CO2 electroreduction to multiple carbon products was significantly improved, and the catalytic effect of high selectivity to ethylene was achieved. The Faraday efficiency reached 28.8%, and the Faraday efficiency of carbon-containing products reached more than 50%.
Smart Images

Figure CN119243208A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic materials for controlling atmospheric pollutants, and in particular relates to a pulse current enhanced MOF-based catalyst and a preparation method and application thereof. Background Art
[0002] The storage and efficient conversion and utilization technologies of CO2 are particularly important. They are not only key means to mitigate climate change, but also an important direction to promote the development of new energy industries.
[0003] As a stable and readily available energy source, electricity has great potential for the catalytic conversion of CO2 through electric drive. It can not only convert this greenhouse gas into valuable chemicals or fuels, but also achieve zero emissions in the energy storage and conversion process, which is of great significance for building a low-carbon circular economy system. However, the current development of CO2 electroreduction technology still faces many bottlenecks, the most prominent of which is the limitation of product distribution.
[0004] At present, the products of CO2 electroreduction are mainly concentrated in single-carbon products with low added value such as CO and methane. In order to achieve high-value utilization of CO2 resources, scientists are committed to exploring catalytic systems that can promote CC bond coupling in order to obtain di-carbon or even multi-carbon products with higher value.
[0005] Copper-based catalysts are considered to be one of the effective ways to achieve the conversion of CO2 to multi-carbon products, but they still face severe challenges in practical applications. First, the product selectivity of Cu-based catalysts is poor, that is, multiple products are often generated simultaneously under the same reaction conditions, making it difficult to efficiently and directional synthesize the target product; second, the activity of Cu-based catalysts needs to be improved to meet the efficiency and output requirements of industrial production. Therefore, how to design and optimize Cu-based catalysts to improve their selectivity and catalytic activity for specific multi-carbon products has become a key scientific issue that needs to be urgently addressed in the current field of CO2 electroreduction. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a pulse current enhanced MOF-based catalyst and its preparation method and application, which solves the problems of poor product selectivity and low activity faced by Cu-based catalysts when performing CO2 electroreduction to multi-carbon products.
[0007] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for preparing a pulse current enhanced MOF-based catalyst, comprising: Dissolving copper salt and polyvinyl pyrrolidone in a mixed solution of N,N-dimethylformamide and ethanol, and then adding formic acid to obtain solution A; Dissolving Cu-TCPP in a mixed solution of DMF and ethanol to obtain solution B; The A solution and the B solution are dispersed evenly, and heated and dried to obtain PML-Cu; Under inert atmosphere, PML-Cu was calcined to obtain PML-CuNPs; Under inert atmosphere conditions, PML-CuNPs were treated with pulse current to obtain Pulse-PML-CuNPs.
[0008] The mass ratio of the copper salt, polyvinyl pyrrolidone and Cu-TCPP is (20-25):100:(45-50).
[0009] The copper salt is Cu(NO3)2·3H2O or CuCl2·2H2O.
[0010] The A solution and the B solution are dispersed uniformly, and heated and dried to obtain PML-Cu, specifically: Solution A and solution B are mixed and dispersed evenly, and heated in an oven at 80-100°C for 8-10 hours.
[0011] The step of calcining PML-Cu in an inert gas to obtain PML-CuNPs is as follows: In an inert gas, PML-Cu was calcined at 250-280 °C for 2-3 h to obtain PML-CuNPs.
[0012] Pulse-PML-CuNPs were obtained by treating PML-CuNPs with pulse current, specifically: PML-CuNPs are dispersed in a volatile solvent and then coated on a working electrode. Under inert atmosphere conditions, a three-electrode system is used to treat the PML-CuNPs with a pulse current in an electrolyte to obtain Pulse-PML-CuNPs.
[0013] The PML-CuNPs are treated by pulse current to obtain Pulse-PML-CuNPs, specifically: Pulse-PML-CuNPs were obtained by pulse current treatment with a lower limit of -0.5 V and an upper limit of +1 V, starting from a negative potential and pulsing once every 1 s for 30 s.
[0014] The electrolyte is a 0.1-0.2 mol / L KHCO3 solution.
[0015] The present invention also provides a pulse current enhanced MOF-based catalyst prepared by the above preparation method.
[0016] The present invention also provides the application of the above-mentioned pulse current enhanced MOF-based catalyst in the field of CO2 electroreduction.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a pulse current enhanced MOF-based catalyst. The method generates active centers in situ in a two-dimensional MOF-based material Cu-TCPP by an in-situ reduction method of a node metal, without the need for external active sites, and is easy to operate. The synthesized two-dimensional MOF-based electrocatalyst PML-CuNPs has a single atomic layer structure, can maximize the mass transfer rate, and greatly improve the reaction rate; the present invention also changes the surface state of the active center by a pulse current method, changes the surface roughness and valence state of the Cu nanoparticles, enhances the reaction selectivity of CO2 electroreduction to multi-carbon products, and achieves the result of high product selectivity to ethylene.
[0018] The pulse current enhanced MOF-based catalyst provided by the present invention is subjected to pulse current treatment. Under oxidation potential conditions, the surface of CuNPs will be partially oxidized, and under reduction potential conditions, partial reduction will occur. After multiple pulses, the CuNPs will present an uneven distribution of oxidized and reduced Cu, which increases the surface roughness of the catalyst and increases the distribution ratio of oxidized Cu. Studies have shown that oxidized Cu is more conducive to the production of multi-carbon products.
[0019] The catalyst prepared by the present invention is used for the catalytic reaction of CO2 electroreduction to multi-carbon products. At the optimal potential, the Faraday efficiency of ethylene reaches 28.8%, and the Faraday efficiency of carbon-containing products reaches more than 50%. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for use in the embodiment: Figure 1 The schematic diagram of the catalyst prepared by the present invention for electrocatalytic reduction of CO2 to C2H4; Figure 2 is the voltage curve during the pulse treatment process of the present invention; Figure 3 The distribution diagram of the electrocatalytic CO2 reduction products of PML-CuNPs prepared in Example 1 in 0.1 mol / L KHCO3 electrolyte; Figure 4 The distribution diagram of the electrocatalytic CO2 reduction products of Pulse-PML-CuNPs prepared in Example 2 in 0.1 mol / L KHCO3 electrolyte; Figure 5This is the distribution diagram of the electrocatalytic CO2 reduction products of Pulse-PML-CuNPs prepared in Example 3 under 0.5 mol / L KHCO3 electrolyte conditions. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] Metal organic frameworks (MOFs) are a new type of crystalline porous materials, whose metal nodes and bridging ligands have good designability and tailorability. They can be applied in different scenarios through the rational combination and functionalization of different components. Therefore, MOF-based materials have received widespread attention in many fields.
[0023] The present invention is based on a two-dimensional MOF with Cu as the metal node. By annealing in a low-temperature N2 atmosphere, the Cu of a part of the nodes is reduced to Cu nanoparticles. Then, a pulse current is used for further treatment to change the surface roughness and valence state of the Cu nanoparticles, thereby achieving the coexistence of oxidized and reduced copper on the surface of the Cu nanoparticles, and enhancing the catalyst performance of CO2 electroreduction to multi-carbon products.
[0024] The present invention will be further described below in conjunction with the accompanying drawings: A method for preparing a pulse current enhanced MOF-based catalyst comprises the following steps: Dissolve copper salt and polyvinyl pyrrolidone in a mixed solution of N,N-dimethylformamide (DMF) and ethanol, and then add formic acid to obtain solution A; Dissolving Cu-TCPP in a mixed solution of DMF and ethanol to obtain solution B; The A solution and the B solution were dispersed evenly, and heated and dried to obtain a purple-red powder, which was named PML-Cu; Under inert atmosphere, PML-Cu was calcined to obtain red powder, which was named PML-CuNPs; Under inert atmosphere, PML-CuNPs were treated with pulse current to obtain powder, which was named Pulse-PML-CuNPs.
[0025] The present invention is further explained below: In some embodiments, the addition ratio of copper salt, polyvinyl pyrrolidone and Cu-TCPP is: (20-25) : 100 : (45-50). It should be noted that an appropriate amount of copper salt can ensure that there are enough copper ions to bind to the TCPP ligand to form a stable and functional Cu-TCPP complex; the amount of polyvinyl pyrrolidone can effectively disperse and stabilize other components without having too much negative impact on the system.
[0026] In some embodiments, the copper salt is Cu(NO3)2·3H2O or CuCl2·2H2O. It should be noted that these two copper salts have good solubility and provide copper ions required for the reaction.
[0027] In some embodiments, the mixing ratio of N,N-dimethylformamide and ethanol is (2-3):1.
[0028] In some embodiments, the A solution and the B solution are dispersed uniformly, heated and dried to obtain a purple-red powder, which is denoted as PML-Cu, specifically: Solution A and solution B are placed in a polytetrafluoroethylene-lined reactor and mixed evenly, and heated in an oven at 80-100°C for 8-10 hours. It should be noted that the reaction rate and product yield can be controlled and the structure and properties of PML-Cu can be adjusted by appropriate temperature and heating time.
[0029] In some embodiments, the PML-Cu is calcined in an inert gas to obtain a red powder, specifically: Under inert atmosphere, PML-Cu is placed in a heat-resistant container (magnetic boat, crucible, etc.), put into a tube furnace, and calcined at 250-280°C for 2-3 hours to obtain a red powder, which is recorded as PML-CuNPs. It should be noted that PML-Cu reduces the Cu at a part of the nodes to Cu nanoparticles by calcining at this temperature and time, and the Cu nanoparticles are evenly distributed in the PML matrix. The obtained PML-CuNPs have a single atomic layer structure, which can maximize the mass transfer rate.
[0030] In some embodiments, PML-CuNPs are treated with pulse current under inert atmosphere, and the obtained product is recorded as Pulse-PML-CuNPs, specifically: PML-CuNPs are dispersed in a volatile solvent (ethanol, methanol, acetone, etc.) and then coated on carbon paper or carbon cloth as a working electrode. Using a three-electrode system (Ag / AgCl electrode as a reference electrode, Pt electrode as a counter electrode, and a working electrode), PML-CuNPs are treated with a pulse current in an electrolyte under inert atmosphere to obtain Pulse-PML-CuNPs.
[0031] The lowest potential of the pulse current is -0.5V, the highest potential is +1.0V, and the pulse current is pulsed once every 1s from the negative potential, and the PML-CuNPs are pulsed for 30s to obtain Pulse-PML-CuNPs. It should be noted that the surface of CuNPs will be partially oxidized under the oxidation potential condition, and partially reduced under the reduction potential. After multiple pulses, the CuNPs will show an uneven distribution of oxidized and reduced Cu, which increases the roughness of the catalyst surface and increases the distribution ratio of oxidized Cu. Oxidized Cu is more conducive to the production of multi-carbon products.
[0032] The electrolyte is a 0.1-0.2 mol / L KHCO3 solution.
[0033] Electrocatalytic CO2 reduction reaction: Using a three-electrode system, the prepared catalyst was coated on carbon paper as a working electrode. In a KHCO3 solution and a CO2 atmosphere, CO2 was electroreduced to multi-carbon products, and the performance was tested.
[0034] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific examples.
[0035] In the following examples, unless otherwise specified, all materials used can be obtained through common channels; and the test methods adopted are conventional methods in the art.
[0036] Example 1 PML-Cu: Dissolve 2.4mgCu(NO3)2·3H2O and 10mg polyvinylpyrrolidone in a mixed solution of 9ml N,N-dimethylformamide (DMF) and 3ml ethanol, and then add 40ul formic acid, which is called solution A. Weigh 4.7mg Cu-TCPP and dissolve it in a mixed solution of 3ml DMF and 1ml ethanol, which is called solution B. Mix A and B in a polytetrafluoroethylene-lined reactor, place in an oven at 80℃ for 8 hours, cool, wash with ethanol, and dry to obtain a purple-red powder, which is recorded as PML-Cu.
[0037] PML-CuNPs: Weigh 20 mg of PML-Cu in a magnetic boat, put it into a tube furnace, and calcine it at 250 °C for two hours under nitrogen atmosphere to obtain a red powder, which is recorded as PML-CuNPs; The electrocatalytic CO2 reduction reaction performed by the catalyst prepared in this example was carried out in a 0.1 mol / L KHCO3 electrolyte.
[0038] Example 2 PML-Cu: 4.8mgCu(NO3)2·3H2O and 20mg polyvinylpyrrolidone were dissolved in a mixed solution of 18ml N,N-dimethylformamide (DMF) and 6ml ethanol, and then 80ul formic acid was added to be called solution A. 9.4mg Cu-TCPP was weighed and dissolved in a mixed solution of 6ml DMF and 2ml ethanol, which was called solution B. A and B were mixed in a polytetrafluoroethylene-lined reactor, placed in an oven at 80℃ for 8 hours, cooled, washed with ethanol, and dried to obtain a purple-red powder, which was recorded as PML-Cu.
[0039] PML-CuNPs: Weigh 20 mg of PML-Cu in a magnetic boat, put it into a tube furnace, and calcine it at 260 °C for 2 h under nitrogen atmosphere to obtain a red powder, which is recorded as PML-CuNPs; Pulse-PML-CuNPs: PML-CuNPs were dispersed in ethanol and coated on carbon paper. A three-electrode system (Ag / AgCl electrode as reference electrode, Pt electrode as counter electrode, catalyst coated on carbon paper as working electrode) was used to treat PML-CuNPs in 0.1 mol / L KHCO3 solution under N2 atmosphere with a pulse current of -0.5 V and +1 V. Pulse-PML-CuNPs were obtained after treatment. The voltage changes with time as shown in Figure 2 shown.
[0040] The electrocatalytic CO2 reduction reaction performed by the catalyst prepared in this example was carried out in a 0.1 mol / L KHCO3 electrolyte.
[0041] Example 3 PML-Cu: Dissolve 2.4mgCu(NO3)2·3H2O and 10mg polyvinylpyrrolidone in a mixed solution of 9ml N,N-dimethylformamide (DMF) and 3ml ethanol, and then add 40ul formic acid, which is called solution A. Weigh 4.7mg Cu-TCPP and dissolve it in a mixed solution of 3ml DMF and 1ml ethanol, which is called solution B. Mix A and B in a polytetrafluoroethylene-lined reactor and place it in an oven at 80℃ for 10 hours. After cooling, wash with ethanol and dry to obtain a purple-red powder, which is recorded as PML-Cu.
[0042] PML-CuNPs: Weigh 20 mg of PML-Cu in a magnetic boat, put it into a tube furnace, and calcine it at 280 °C for two hours under nitrogen atmosphere to obtain a red powder, which is recorded as PML-CuNPs; Pulse-PML-CuNPs: PML-CuNPs were dispersed in ethanol and coated on carbon paper. A three-electrode system (Ag / AgCl electrode as reference electrode, Pt electrode as counter electrode, catalyst coated on carbon paper as working electrode) was used to treat PML-CuNPs with a pulse current of -0.5V and +1V in a 0.2mol / L KHCO3 solution and N2 atmosphere. Pulse-PML-CuNPs were obtained after treatment. The voltage changes with time as shown in Figure 2 shown.
[0043] The electrocatalytic CO2 reduction reaction performed by the catalyst prepared in this example was carried out in a 0.5 mol / L KHCO3 electrolyte.
[0044] like Figure 3 and Figure 4 As shown in the figure, the catalytic results show that the electro-reduction product of the Pulse-PML-CuNPs catalyst after pulse treatment is mainly ethylene. At the optimal potential, the Faraday efficiency of ethylene reaches 28.8%, and the Faraday efficiency of carbon-containing products reaches more than 50%. The electro-reduction products of the PML-CuNPs catalyst that has not been pulse treated are mainly single-carbon products such as CO and methane, and the Faraday efficiency of ethylene is only 12.9%. There are large differences in the types of reduction products and Faraday efficiencies between the two, which are closely related to the surface roughness and valence state of the active center Cu. After pulse treatment, the surface of CuNPs will be partially oxidized under oxidation potential conditions, and partially reduced under reduction potential. After multiple pulses, CuNPs will show an uneven distribution of oxidized and reduced Cu, which increases the surface roughness of the catalyst and increases the distribution ratio of oxidized Cu. Studies have shown that oxidized Cu is more conducive to the production of multi-carbon products.
[0045] like Figure 5 As shown in the figure, in the 0.5 mol / L KHCO3 electrolyte, the Faraday efficiency of ethylene at the optimal potential is only 22.1%. The buffering capacity of 0.5 mol / L KHCO3 is weaker than that of 0.1 mol / L KHCO3, and the pH on the electrode surface will be higher, which is not conducive to the production of multi-carbon products.
[0046] Example 4 PML-Cu: Dissolve 4mgCu(NO3)2·3H2O and 20mg polyvinylpyrrolidone in a mixed solution of 18ml N,N-dimethylformamide (DMF) and 6ml ethanol, and then add 80ul formic acid, which is called solution A. Weigh 10mg Cu-TCPP and dissolve it in a mixed solution of 6ml DMF and 2ml ethanol, which is called solution B. Mix A and B in a polytetrafluoroethylene-lined reactor, place in an oven at 100℃ for 10 hours, cool, wash with ethanol, and dry to obtain a purple-red powder, which is recorded as PML-Cu.
[0047] PML-CuNPs: Weigh 20 mg of PML-Cu in a magnetic boat, put it into a tube furnace, and calcine it at 280 °C for 3 h under nitrogen atmosphere to obtain a red powder, which is recorded as PML-CuNPs; Pulse-PML-CuNPs: PML-CuNPs were dispersed in ethanol and coated on carbon paper. A three-electrode system (Ag / AgCl electrode as reference electrode, Pt electrode as counter electrode, catalyst coated on carbon paper as working electrode) was used to treat PML-CuNPs with a pulse current of -0.5V and +1V in a 0.2mol / L KHCO3 solution and N2 atmosphere. Pulse-PML-CuNPs were obtained after treatment. The voltage changes with time as shown in Figure 2 shown.
[0048] Example 5 PML-Cu: Dissolve 5mgCu(NO3)2·3H2O and 20mg polyvinylpyrrolidone in a mixed solution of 18ml N,N-dimethylformamide (DMF) and 6ml ethanol, and then add 80ul formic acid, which is called solution A. Weigh 9mg Cu-TCPP and dissolve it in a mixed solution of 6mlDMF and 2ml ethanol, which is called solution B. Mix A and B in a polytetrafluoroethylene-lined reactor, place in a 90℃ oven for 10 hours, cool, wash with ethanol, and dry to obtain a purple-red powder, which is recorded as PML-Cu.
[0049] PML-CuNPs: Weigh 20 mg of PML-Cu in a magnetic boat, put it into a tube furnace, and calcine it at 260 °C for 3 h under nitrogen atmosphere to obtain a red powder, which is recorded as PML-CuNPs; Pulse-PML-CuNPs: PML-CuNPs were dispersed in ethanol and coated on carbon paper. A three-electrode system (Ag / AgCl electrode as reference electrode, Pt electrode as counter electrode, catalyst coated on carbon paper as working electrode) was used to treat PML-CuNPs in 0.1 mol / L KHCO3 solution under N2 atmosphere with a pulse current of -0.5 V and +1 V. Pulse-PML-CuNPs were obtained after treatment. The voltage changes with time as shown in Figure 2 shown.
[0050] Example 6 PML-Cu: Dissolve 4.8mgCu(NO3)2·3H2O and 20mg polyvinylpyrrolidone in a mixed solution of 18ml N,N-dimethylformamide (DMF) and 6ml ethanol, and then add 80ul formic acid, which is called solution A. Weigh 9.2mg Cu-TCPP and dissolve it in a mixed solution of 6ml DMF and 2ml ethanol, which is called solution B. A and B are mixed in a polytetrafluoroethylene-lined reactor, placed in an oven at 100℃ for 9 hours, cooled, washed with ethanol, and dried to obtain a purple-red powder, which is recorded as PML-Cu.
[0051] PML-CuNPs: Weigh 20 mg of PML-Cu in a magnetic boat, put it into a tube furnace, and calcine it at 270 °C for 2 h under nitrogen atmosphere to obtain a red powder, which is recorded as PML-CuNPs; Pulse-PML-CuNPs: PML-CuNPs were dispersed in ethanol and coated on carbon paper. A three-electrode system (Ag / AgCl electrode as reference electrode, Pt electrode as counter electrode, catalyst coated on carbon paper as working electrode) was used to treat PML-CuNPs in 0.1 mol / L KHCO3 solution under N2 atmosphere with a pulse current of -0.5 V and +1 V. Pulse-PML-CuNPs were obtained after treatment. The voltage changes with time as shown in Figure 2 shown.
[0052] Example 7 PML-Cu: Dissolve 4.8mgCuCl2·2H2O and 20mg polyvinylpyrrolidone in a mixed solution of 18ml N,N-dimethylformamide (DMF) and 6ml ethanol, and then add 80ul formic acid, which is called solution A. Weigh 9.4mg Cu-TCPP and dissolve it in a mixed solution of 6mlDMF and 2ml ethanol, which is called solution B. Mix A and B in a polytetrafluoroethylene-lined reactor, place in an oven at 100℃ for 10 hours, cool, wash with ethanol, and dry to obtain a purple-red powder, which is recorded as PML-Cu.
[0053] PML-CuNPs: Weigh 20 mg of PML-Cu in a magnetic boat, put it into a tube furnace, and calcine it at 280 °C for 3 h under nitrogen atmosphere to obtain a red powder, which is recorded as PML-CuNPs; Pulse-PML-CuNPs: PML-CuNPs were dispersed in ethanol and coated on carbon paper. A three-electrode system (Ag / AgCl electrode as reference electrode, Pt electrode as counter electrode, catalyst coated on carbon paper as working electrode) was used to treat PML-CuNPs in 0.1 mol / L KHCO3 solution under N2 atmosphere with a pulse current of -0.5 V and +1 V. Pulse-PML-CuNPs were obtained after treatment. The voltage changes with time as shown in Figure 2 shown.
[0054] The endpoints and any values of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, the endpoint values of each scope, the endpoint values of each scope and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.
[0055] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art can still modify or make equivalent substitutions to the specific implementations of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention are within the scope of protection of the claims of the present invention to be approved.
Claims
1. A method for preparing a pulse current enhanced MOF-based catalyst, characterized in that: include: Dissolving copper salt and polyvinyl pyrrolidone in a mixed solution of N,N-dimethylformamide and ethanol, and then adding formic acid to obtain solution A; Dissolving Cu-TCPP in a mixed solution of DMF and ethanol to obtain solution B; The A solution and the B solution are dispersed evenly, and heated and dried to obtain PML-Cu; Under inert atmosphere, PML-Cu was calcined to obtain PML-CuNPs; Under inert atmosphere conditions, PML-CuNPs were treated with pulse current to obtain Pulse-PML-CuNPs.
2. The method for preparing a pulse current enhanced MOF-based catalyst according to claim 1, characterized in that: The mass ratio of the copper salt, polyvinyl pyrrolidone and Cu-TCPP is (20-25):100:(45-50).
3. The method for preparing a pulse current enhanced MOF-based catalyst according to claim 1, characterized in that: The copper salt is Cu(NO3)2·3H2O or CuCl2·2H2O.
4. The method for preparing a pulse current enhanced MOF-based catalyst according to claim 1, characterized in that: The A solution and the B solution are dispersed uniformly, and heated and dried to obtain PML-Cu, specifically: Solution A and solution B are mixed and dispersed evenly, and heated in an oven at 80-100°C for 8-10 hours.
5. The method for preparing a pulse current enhanced MOF-based catalyst according to claim 1, characterized in that: The step of calcining PML-Cu in an inert gas to obtain PML-CuNPs is as follows: In an inert gas, PML-Cu was calcined at 250-280 °C for 2-3 h to obtain PML-CuNPs.
6. The method for preparing a pulse current enhanced MOF-based catalyst according to claim 1, characterized in that: Pulse-PML-CuNPs were obtained by treating PML-CuNPs with pulse current, specifically: PML-CuNPs are dispersed in a volatile solvent and then coated on a working electrode. Under inert atmosphere conditions, a three-electrode system is used to treat the PML-CuNPs with a pulse current in an electrolyte to obtain Pulse-PML-CuNPs.
7. The method for preparing a pulse current enhanced MOF-based catalyst according to claim 6, characterized in that: The PML-CuNPs are treated by pulse current to obtain Pulse-PML-CuNPs, specifically: Pulse-PML-CuNPs were obtained by pulse current treatment with a lower limit of -0.5 V and an upper limit of +1 V, starting from a negative potential and pulsing once every 1 s for 30 s.
8. The method for preparing a pulse current enhanced MOF-based catalyst according to claim 6, characterized in that: The electrolyte is a 0.1-0.2 mol / L KHCO3 solution.
9. A pulse current enhanced MOF-based catalyst prepared according to the preparation method according to any one of claims 1 to 8.
10. Application of the pulse current enhanced MOF-based catalyst according to claim 9 in the field of CO2 electroreduction.
Citation Information
Patent Citations
Preparation method for electrocatalytic carbon dioxide reduction electrode, and application thereof
CN108866561A
Cu-MOF material for electrocatalytic reduction of CO2 and preparation method of Cu-MOF material
CN113355688A
Preparation methods and application of copper-based MOF catalyst and carbon-coated copper-based MOF catalyst
CN113913865A
Preparation method and application of in-situ growth carbon dioxide electroreduction electrocatalyst
CN117127207A
Preparation method of carbon dioxide electroreduction catalyst
CN118007162A
Cited By
Pulse current-enhanced MOF-based catalyst, preparation method therefor and use thereof
WO2026066208A1